Chemoselective Reduction of Phosphine Oxides by 1, 3‐Diphenyl‐Disiloxane. Issue 58 (18th September 2017) - Buonomo, Joseph A.; Eiden, Carter G.; Aldrich, Courtney C.
Abstract: Reduction of phosphine oxides to the corresponding phosphines represents the most straightforward method to prepare these valuable reagents. However, existing methods to reduce phosphine oxides suffer from inadequate chemoselectivity due to the strength of the P=O bond and/or poor atom economy. Herein, we report the discovery of the most powerful chemoselective reductant for this transformation to date, 1, 3‐diphenyl‐disiloxane (DPDS ). Additive‐freeDPDS selectively reduces both secondary and tertiary phosphine oxides with retention of configuration even in the presence of aldehyde, nitro, ester, α, β‐unsaturated carbonyls, azocarboxylates, and cyano functional groups. Arrhenius analysis indicates that the activation barrier for reduction byDPDS is significantly lower than any previously calculated silane reduction system. Inclusion of a catalytic Brønsted acid further reduced the activation barrier and led to the first silane‐mediated reduction of acyclic phosphine oxides at room temperature. Abstract : Simple and clean : We report the discovery of the most powerful chemoselective reductant for the reduction of phosphine oxides to the corresponding phosphines to date, 1, 3‐diphenyl‐disiloxane (DPDS ).DPDS could be deployed alone to afford high yields of phosphines from secondary and tertiary phosphine oxides very rapidly or used in tandem with the Brønsted acid bis‐( p ‐nitrophenyl)phosphoric acid (BNPA ) in reductions of acyclic phosphine oxides at ambient temperature.